The Influences Of Transformational Leadership On Employee Performance - Voon, Yee Sien (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study examined the influences of transformational leadership on employee performance in marketing company of Kuching. There are four elements in transformational leadership, which are individualized consideration, inspirational motivation, intellectual stimulation and idealized influence. Data on office employee in marketing company (N=52) were analysed by using central tendencies measurement, Pearson Correlation (r) and linear multiple regression to get for the results. There are moderate relationship found between transformational leadership and job performance; inspirational motivation is the most effective leadership that can improve employee performance of marketing company; while idealized influence is found to have negative effect on employee performance.